2011
DOI: 10.1104/pp.111.188953
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Small Polypeptide Is a Novel Component of DNA-Binding Protein Phosphatase 1-Mediated Resistance to Plum pox virus in Arabidopsis    

Abstract: DNA-binding protein phosphatases (DBPs) have been identified as a novel class of plant-specific regulatory factors playing a role in plant-virus interactions. NtDBP1 from tobacco (Nicotiana tabacum) was shown to participate in transcriptional regulation of gene expression in response to virus infection in compatible interactions, and AtDBP1, its closest relative in the model plant Arabidopsis (Arabidopsis thaliana), has recently been found to mediate susceptibility to potyvirus, one of the most speciose taxa o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…Sequencing of individual clones confirmed that there were no errors in the SCS9 cDNA. p423 GAL1/SCS9, p423 GAL1/SCS9-GFP and the respective empty vectors were transformed into wild-type (BMA64, MATα; [ 13 ]) and trm7p (YBL4409, MATα, trm7Δ:TRP1 [ 13 ]) yeast strains as previously described [ 59 ] and grown on minimal medium agar plates lacking His. Individual yeast transformants were then transferred to selective liquid media containing 2% (w/v) Gal to induce expression of SCS9 .…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing of individual clones confirmed that there were no errors in the SCS9 cDNA. p423 GAL1/SCS9, p423 GAL1/SCS9-GFP and the respective empty vectors were transformed into wild-type (BMA64, MATα; [ 13 ]) and trm7p (YBL4409, MATα, trm7Δ:TRP1 [ 13 ]) yeast strains as previously described [ 59 ] and grown on minimal medium agar plates lacking His. Individual yeast transformants were then transferred to selective liquid media containing 2% (w/v) Gal to induce expression of SCS9 .…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, in the present study, we found that 963 AS events significantly responded to the combination of heat and drought stress but barely changed under individual HS and DS, suggesting that these HD‐specific AS responses might be caused by the interaction between drought and heat responses (Clusters 10–12 in Figure c). Interestingly, several previously reported stress‐responsive genes also exhibited HD‐specific AS response, for example TNO1 (involved in salt tolerance), WDR5A (involved in drought tolerance), AL5 (involved in salt, drought and freezing tolerance) and DBP1 (involved in virus resistance) (Figure S3, Data S1) (Castello et al ., ; Kim and Bassham, ; Liu et al ., ; Wei et al ., ). Moreover, some GO terms, such as ‘glutathione biosynthetic process’ and ‘DNA methylation’, significantly enriched HD‐specific AS genes, indicating that these processes tended to be responsive to the combination of heat and drought stress at AS level (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the physical interactions involved have not been studied in detail, both eIF(iso)4E and eIF(iso)4G1 have been shown to be absolutely required for successful PPV infection in Arabidopsis (Decroocq et al ., ; Nicaise et al ., ), a situation that parallels that observed for many other potyviruses. In the specific cases of PPV and Turnip mosaic virus , two further proteins have been shown to partially affect viral accumulation, probably through their effect on eIF(iso)4E accumulation: the DNA‐binding protein phosphatase AtDBP1 (Castelló et al ., ) and a small interactor of AtDBP1, DIP2 (Castelló et al ., ).…”
Section: Interactome Studies and The Identification Of Host Factors Cmentioning
confidence: 97%